2014
DOI: 10.1155/2014/695014
|View full text |Cite
|
Sign up to set email alerts
|

Is Lipid Profile Associated with Bone Mineral Density and Bone Formation in Subjects with Spinal Cord Injury?

Abstract: Purpose. The association between serum lipids and bone mineral density (BMD) has been investigated previously but, up to now, these relationships have not yet been described in spinal cord injury (SCI). We tried to assess the correlation between serum triglyceride (TG), total cholesterol (TC), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) and BMD in male subjects with SCI. Methods. Dual-energy X-ray absorptiometry (DXA) was used to assess BMD in femoral neck, trochanter, intertrochanteric z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A few studies found no association and/or a positive association with serum cholesterol and LDL cholesterol ( 98 101 ). The summarized data from all the studies indicate that there is an existence of an inconsistent relationship for the case of HDL cholesterol and BMD ( 6 , 99 , 100 , 102 ). In several clinical trials, but not in all, the use of statins have been associated with a reduction of fracture risk, and the patients taking statins having a higher BMD than those who do not ( 103 – 105 ).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies found no association and/or a positive association with serum cholesterol and LDL cholesterol ( 98 101 ). The summarized data from all the studies indicate that there is an existence of an inconsistent relationship for the case of HDL cholesterol and BMD ( 6 , 99 , 100 , 102 ). In several clinical trials, but not in all, the use of statins have been associated with a reduction of fracture risk, and the patients taking statins having a higher BMD than those who do not ( 103 – 105 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association between serum lipids and BMD has been investigated in previous studies [5][6][7]. Hadis et al [5] investigated the relationships between serum lipids and BMD in 85 male patients with spinal cord injury (SCI).…”
Section: Discussionmentioning
confidence: 99%
“…The association between serum lipids and BMD has been investigated in previous studies [5][6][7]. Hadis et al [5] investigated the relationships between serum lipids and BMD in 85 male patients with spinal cord injury (SCI). As a result of this study a positive correlation between HDL and femoral neck BMD (r = 0.33, p = 0.004) was found although any a relation between others and BMD scores had no.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hepatocyte lipids are stored or metabolized to produce energy or made available for other tissues. It has been shown a strict relationship among serum lipid profile, bone and adipose tissues, for instance, a positive correlation has been found between HDL and femoral neck mineral density, and a negative association between HDL and osteocalcin in male subject with spinal cord injury [31]. Moreover, bone cells have been shown to utilize lipid metabolism, while previously it was assumed that bone cells utilized mainly glucose metabolism [32].…”
Section: Lipidsmentioning
confidence: 99%